Asuhan Akupunktur pada Penderita Nyeri Pinggang di Klinik Jayapura Holistic Therapy - Mukhlis Mukhlis; Puspo Wardoyo; Chantika Mahadini (ARTERI : Jurnal Ilmu Kesehatan, 2026)
Low back pain is a common musculoskeletal disorder that can reduce a patient's quality of life. From the perspective of Traditional Chinese Medicine (TCM), this condition is often associated with Cold-Damp Bi syndrome accompanied by Qi and Xue stagnation and Yang deficiency. This study aims to determine the scale of back pain in participants before and after receiving acupuncture treatment. The research method used was a case study, acupuncture treatment approach at the Shenshu (BL23), Dachangshu (BL25), and Weizhong (BL40) points for 20 minutes, performed six times with a 3-day interval between sessions. Evaluation was carried out using a Visual Analog Scale (VAS) pain measurement tool. The results showed a gradual decrease in pain intensity from a scale of 8 in the first session to a scale of 2 in the sixth session, with a total reduction of 75%. In addition, there was an improvement in tenderness, as well as an increase in the patient's motor function and activity. The conclusion of this study is that acupuncture treatment is effective in reducing low back pain from a scale of 8 (severe pain) at the beginning of the session to a scale of 2 (mild pain) at the end of the sixth session. This therapy can be a safe alternative treatment for musculoskeletal pain.